Expanding the cattle reference graph genome - Talenti, A.; Powell, J.; Wragg, D.; Paxton, E.; Chepkwony, M.; Miyunga, Antoinette; Njeru, R.; Hemmink, Johanneke D.; Fisch, A.; Ferreira, B.R.; Hammond, J.A.; Archibald, A.L.; et al. (Wageningen University & Research, 2022)
Recent studies have highlighted several key advantages of graph genomes over standard linear reference genomes. These advantages include improvements in read mapping rates at divergent loci and the ability to more accurately call structural variants. However, the availability of graph genomes that represent the extensive diversity of livestock species remain limited. To address this limitation, we have incorporated 15 cattle genomes into an expanded cattle graph genome, including 8 completely novel high-quality cattle assemblies from 4 divergent breeds (Holstein-Friesian, N'Dama, Boran and Nelore), each with high contiguity (N50>10 Mb). This graph genome incorporates over 250 Mb (9.5%) of novel sequence across the primary chromosomes, providing a better reference representation of the bovine pangenome and a key resource for the livestock community.